Assessment of Entrepreneurial Orientation in Vocational Training Students: Development of a New Scale and Relationships With Self-Efficacy and Personal Initiative - Gorostiaga, Arantxa; Aliri, Jone; Ulacia, Imanol; Soroa, Goretti; Balluerka, Nekane; Aritzeta, Aitor; Muela, Alexander (Frontiers in Psychology, 2019)
Having emerged as an important concept in the organizational field, entrepreneurial orientation has also become a key idea in the context of education. Indeed, entrepreneurial education is now one of the common objectives for education and training systems in the European Union. Despite its importance, however, there is a scarcity of valid and reliable measures for assessing entrepreneurial orientation in students. The present study aimed to address this by developing and examining the psychometric properties of the Entrepreneurial Orientation Scale (EOS). A second objective is to study the relationships between entrepreneurial orientation and gender, self-efficacy, and personal initiative. The sample comprised 411 vocational training students (50.36% male, 49.64% female). The final version of the instrument comprised 32 items assessing six dimensions: innovativeness, risk-taking, proactiveness, competitiveness, achievement orientation, and learning orientation. The EOS showed good psychometric properties and its dimensions demonstrated concurrent relationships with self-efficacy and personal initiative. The EOS may be used to measure entrepreneurial orientation in the educational context and to evaluate interventions designed to promote an entrepreneurial spirit in schools, colleges, and universities.